Mathematical model of biodegradation process of sewage due to addition of chlorides. Issue 25 (27th May 2016) - Rami Reddy, T.S.; Gupta, A.B.
Abstract: Biodegradation plays a key role in the environmental risk assessment of organic matter. The need to assess biodegradability of organic matter for regulatory purpose can be ably supported by the development of a model for predicting the extent of improvement or inhibition of the process. A mathematical model was developed in order to describe the ratios of BOD5 exertion under varying chloride concentrations compared to those at zero additional chloride values, which indicated the best fit in a polynomial third order equation. It reflected closely both the stimulation as well as inhibition effects under varied chloride concentrations. The model was duly validated by both primary data, acquired through an organized set of controlled laboratory experiments, as well as secondary data reported in the literature. The results indicate a peak value of the ratio at 0.8 g/L, while inhibition started at 6 g/L of chloride concentration. The model can be used as an aid for the design and prediction of sewage treatment process under different salt concentrations. It may help develop strategies for the co-treatment of domestic sewage and R.O. rejects as well as high salt containing industrial wastewaters.